Ekstraksi Kitosan dari Jamur Tiram (Pleurotus ostreatus) serta Karakterisasi Fisikokimia dan Uji Aktivitas Antibakterinya - Dahlia Hasibuan; Ridwanto Ridwanto; Anny Sartika Daulay; Ainil Fithri Pulungan (Journal of Pharmaceutical and Sciences, 2026)
Background: Chitosan is a biopolymer derived from the deacetylation of chitin, which is generally obtained from crustacean waste. However, the utilization of more environmentally friendly alternative sources such as oyster mushrooms (Pleurotus ostreatus) has recently been developed. Chitosan exhibits biocompatible, biodegradable properties and antibacterial activity, making it potentially applicable in the food and pharmaceutical industries. Objective: This study aims to extract and characterize chitosan from oyster mushrooms and to evaluate its antibacterial activity against Escherichia coli. Methods: The study was conducted through extraction stages including deproteinization, depigmentation, demineralization, and deacetylation. Chitosan characterization included functional group analysis using FTIR, as well as physicochemical parameter testing such as yield, moisture content, ash content, and solubility. Antibacterial activity was tested using the disc diffusion method at various chitosan concentrations (0.3%, 0.5%, 0.7%, and 0.9%). Results: The obtained chitosan had a degree of deacetylation of 80.64%, indicating successful conversion of chitin into chitosan. The physicochemical characteristics met quality standards, with a yield of 52.84%, moisture content of 0.666%, and ash content of 0.416%. Chitosan was soluble in 2% acetic acid. Antibacterial testing demonstrated inhibitory activity against Escherichia coli, with inhibition zones ranging from 10.1 to 14.2 mm, categorized as strong. Conclusion: Chitosan extracted from oyster mushrooms exhibits good physicochemical characteristics and promising antibacterial activity, indicating its potential as an environmentally friendly alternative material for applications in the food and pharmaceutical fields.